Pengaruh Kualitas Pelayanan Administrasi Kependudukan Terhadap Kepuasan Masyarakat di Desa Pemecutan Kelod Kota Denpasar - Ramayanti Sitanggang; A. A. Gde Raka; I Made Mardika (Public Inspiration : Jurnal Administrasi Publik, 2020)
Excellent service is a demand of the community in assessing the quality of Government services including at the village level. Services are very important so that the community is satisfied with the performance of the Village Government. This study seeks to examine the effect of five dimensions of service quality consisting of reability, responsiveness, assurance, empathy, and tangibles partially and simultaneously on community satisfaction at the Pemecutan Village Office in south, Denpasar. The number of samples used was 100 people, using the Isaac and Michael models. Data were collected using a questionnaire, measuring variables using a Likert scale, scale 5. Test the validity of using the SPSS 24.0 program package for windows and reliability testing using Alpha Cronbach’s. Classical Assumption Test consists of normality test, variance homogeneity test, linearity test, multicollinearity. Test the influence of the independent variable of service quality on the dependent variable of community satisfaction, used the feasibility test of the model with a significance value of the F test results smaller than the level of significance set (α = 0.05). Anova test results, the value of F = 12270 with a probability of sig = 0,000. The results showed that: (1) There was a positive and significant effect of the responsiveness dimension on community satisfaction with a value of 0.466. Sig value. (1-tailed) of 0.005, the probability value of Sig. (1-tailed) or [0.05> 0.005]. (2) There is a positive and significant influence on the reliability dimension to public satisfaction with a value of 0.552, Sig. (1-tailed) of 0,000, the probability value of Sig. (1-tailed) or [0.05> 0,000]. (3) There is a positive and significant effect of the guarantee dimension on community satisfaction with a value of 0.469, Sig. (1-tailed) of 0.005, the probability value of Sig. (1-tailed) or [0.05> 0.005]. (4) There is a positive and significant effect of the assurance dimension on community satisfaction with a value of 0.361, Sig. (1-tailed) of 0,000, the probability value of Sig. (1-tailed) or [0.05> 0,000]. (5) There is a positive and significant effect of the assurance dimension on community satisfaction with a value of 0.385, Sig. (1-tailed) of 0.005, the probability value of Sig. (1-tailed) or [0.05> 0.005]. (6) there are positive and significant influences in the five dimensions of responsiveness, reliability, guarantee, attention and physical ability to Community Satisfaction. The results of the Model Summary table R = 0.628, and the coefficient of Determination (Rsquare) of 0.395, shows that Community Satisfaction (Y) is influenced by 62.8% by the variable Responsiveness (X1), Reliability variable (X2), Guarantee variable (X3), Attention variable (X4) and Physical Ability variable (X5), while the rest (37.2%) are influenced by other factors.